2021
DOI: 10.1093/beheco/araa145
|View full text |Cite
|
Sign up to set email alerts
|

Aerial attack strategies of hawks hunting bats, and the adaptive benefits of swarming

Abstract: Aggregation can reduce an individual’s predation risk, by decreasing predator hunting efficiency or displacing predation onto others. Here, we explore how the behaviors of predator and prey influence catch success and predation risk in Swainson’s hawks Buteo swainsoni attacking swarming Brazilian free-tailed bats Tadarida brasiliensis on emergence. Lone bats including stragglers have a high relative risk of predation, representing ~5% of the catch but ~0.2% of the population. Attacks on the column were no less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 60 publications
(94 reference statements)
6
16
3
Order By: Relevance
“…This, in effect, is an Eulerian rather than Lagrangian approach to targeting, and it is an approach that works only in the context of a suitably dense swarm. This may in turn explain why neither our present study nor our previous study of the same model system 19 found any evidence to suggest that attacks on the swarm were less successful than attacks on lone bats. This runs counter to the usual assumption that predator hunting efficiency declines such that it appears stationary against the distant background.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…This, in effect, is an Eulerian rather than Lagrangian approach to targeting, and it is an approach that works only in the context of a suitably dense swarm. This may in turn explain why neither our present study nor our previous study of the same model system 19 found any evidence to suggest that attacks on the swarm were less successful than attacks on lone bats. This runs counter to the usual assumption that predator hunting efficiency declines such that it appears stationary against the distant background.…”
Section: Discussioncontrasting
confidence: 90%
“…This may in turn explain why neither our present study nor our previous study of the same model system 19 found any evidence to suggest that attacks on the swarm were less successful than attacks on lone bats. This runs counter to the usual assumption that predator hunting efficiency declines as group density increases, owing to the heightened sensory challenge of targeting individual prey 7 .…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations